Rectal Self-Sampling in Non-Clinical Venues for Detection of Sexually Transmitted Infections (STI) among Behaviorally Bisexual Men - Dodge, Brian (2012)
Rectal sexually transmitted infections (STI) are a common health concern for men who have sex with men (MSM) but little is known about these infections among men who had sex with both men and women (MSMW). Self-obtained rectal specimens were collected from a diverse sample of behaviorally bisexual men. From a total sample of 75 bisexual men, 58 collected specimens. A relatively high prevalence of rectal C. trachomatis infection was found. Participants who collected specimens reported overall acceptability and comfort with self-sampling. Future efforts are needed focusing on increasing awareness of and options for rectal STI testing among bisexual men.